Pozycja prawna wojewody w procesie przemian II Rzeczypospolitej - Wojtczak, Krystyna (Studia Prawa Publicznego, 2021)
The article considers the legal status of the voivode during the interwar period, the time of the difficult restoration of the Polish identity and the creation of the Polish state in the post-Partition lands with three separate systems of territorial division and local administration. The legal situation of the office of the voivode is closely related to the establishment of the systemic foundations of the highest Polish authorities (legislative and executive) and local administration (initially, on the territory of the former Kingdom of Poland and then on the gradually annexed former Polish territories). The author refers to both spheres of legal activity of the Polish state at that time. She discusses the primary political acts, i.e. the March Constitution (1921), the April Constitution (1935) and the Constitutional Act (1926), as well as regulations concerning county administrative authorities of the first instance, situated in the then two-tier (ministries – county offices) administrative apparatus. Attention is primarily focused on the acts directly concerning the position of the voivode, i.e. the Act of 2 August 1919, the Regulation of the President of the Republic of 19 January 1928, and executive acts issued on the basis of these, and against whose background the importance of the legal institution of the voivode is presented: during the time of attempts to unify the administrative system (1918–1928), and in the period of changes leading to a uniform organisational structure of voivodship administrative authorities (1928–1939). The analysis makes it possible to state that successive legal conditions strengthened the political position of the voivode. In both periods covered by the analysis, the voivode was a representative of the government (with broader competences in 1928–1939), the executor of orders from individual ministers, the head of state and local government authorities and offices (1918–1928), the head of general administrative bodies subordinate to him, and the supervisory body over local government (1928–1939). The position of the voivode in the interwar period was unquestionably very strong.